2022
DOI: 10.3389/fendo.2022.1000030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perioperative glycemic indicators on outcomes of endovascular treatment for vertebrobasilar artery occlusion

Abstract: ObjectiveEndovascular treatment (EVT) is, to date, the most promising treatment of vertebrobasilar artery occlusion (VBAO). The study aimed to determine the influence of perioperative glucose levels on clinical outcomes in patients with acute VBAO treated with EVT.MethodsWe retrospectively collected consecutive VBAO patients received EVT in 21 stroke centers in China. The associations between perioperative glycemic indicators (including fasting blood glucose[FBG], admission hyperglycemia, stress hyperglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…28 Hyperglycemia may exacerbate oxidative stress, compromise blood-brain barrier integrity post-cerebral ischemia/reperfusion injury, and heighten the risk of brain edema and hemorrhagic transformation, leading to expanded infarct volume and greater neurological deficits. 28…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Hyperglycemia may exacerbate oxidative stress, compromise blood-brain barrier integrity post-cerebral ischemia/reperfusion injury, and heighten the risk of brain edema and hemorrhagic transformation, leading to expanded infarct volume and greater neurological deficits. 28…”
Section: Discussionmentioning
confidence: 99%
“…Our prior research has demonstrated that elevated admission FBG levels are significantly associated with an increased risk of poor outcomes and sICH. 28 Hyperglycemia may exacerbate oxidative stress, compromise blood-brain barrier integrity post-cerebral ischemia/reperfusion injury, and heighten the risk of brain edema and hemorrhagic transformation, leading to expanded infarct volume and greater neurological deficits. 28 Circulation insufficiency emerged as the strongest predictor for PMV in the PAIRS score.…”
Section: Mechanism Of Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies used the stress hyperglycemia ratio (SHR) as a tool to evaluate stress hyperglycemia (15,16). Moreover, many studies have been found that SHR is associated with poor prognosis in AIS patients (17)(18)(19). Recent evidence revealed that elevated SHR was a clinical predictor of stroke-associated pneumonia (9).…”
Section: Introductionmentioning
confidence: 99%